REDESAIN PLASTIC SHREDDER MENGGUNAKAN METODE DFA (DESIGN FOR ASSEMBLY) - restu, fedia (Jurnal Rekavasi, 2023)
The large amount of plastic waste in landfills of around 20% in Batam City has made academics look for ideas on how to minimize the production of plastic waste, especially for households. In order to be able to manually process the plastic shredder itself, a waste shredding machine was created with another name plastic shredder. Where this plastic shredder has been produced in prototype form which aims to improve the design and can simulate in small quantities. The product design process is the initial stage for planning the product or tool to be designed. At the design stage, errors must be minimized. If in the implementation of manufacturing there is a problem. This will take a long time. One method that has been developed to facilitate this is Design for Assembly (DFA). DFA aims to determine the assembly time for each component, so that assembly difficulties can be minimized before the components are produced. This will result in reduced assembly time required to assemble a product. With the Design For Assembly (DFA) method, it will get a simpler time in assembling a product. In the first stage, it took 414.77 seconds with a total of 96 components which were seen in the manual handling and manual insertion tables which were translated into the worksheet analysis, in the second stage the same thing was done as in stage 1, it obtained 266.25 seconds with a total of 74 components. By using DFA several components have been eliminated in the form of reduced bolts and removed side angels.